2020
DOI: 10.3390/molecules25092093
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Effects Induced by Sulforaphane and Allyl Isothiocyanate on P-Glycoprotein Positive and Negative Variants in L1210 Cells

Abstract: Variants of L1210 leukemia cells-namely, parental P-glycoprotein-negative S cells and R and T cells expressing P-glycoprotein, due to selection with vincristine and transfection with the human p-glycoprotein gene, respectively-were used. The responses of these cell variants to two naturally occurring isothiocyanates-sulforaphane (SFN, from cruciferous vegetables) and allyl isothiocyanate (AITC, from mustard, radish, horseradish and wasabi)-were studied. We obtained conflicting results for the cell death effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…In contrast, the studies of Cudazzo et al (2019) and Martins et al (2013) suggested that chloroquine enhanced the uptake of crystal violet dye in a biphasic concentration manner in HaCaT cells but that this biphasic response did not occur using the NRU assay. A similar divergent finding as seen in 2019) was recently made by Kontar et al (2020). They reported that sulforaphane induced biphasic dose responses in three types of L1210 leukemia cells with the MTS cell viability assay, while, at the same time, showing a dose-dependent decrease in cell number, in contrast to the expected increase in cell number.…”
Section: Non-tumor Cellssupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast, the studies of Cudazzo et al (2019) and Martins et al (2013) suggested that chloroquine enhanced the uptake of crystal violet dye in a biphasic concentration manner in HaCaT cells but that this biphasic response did not occur using the NRU assay. A similar divergent finding as seen in 2019) was recently made by Kontar et al (2020). They reported that sulforaphane induced biphasic dose responses in three types of L1210 leukemia cells with the MTS cell viability assay, while, at the same time, showing a dose-dependent decrease in cell number, in contrast to the expected increase in cell number.…”
Section: Non-tumor Cellssupporting
confidence: 83%
“…They reported that sulforaphane induced biphasic dose responses in three types of L1210 leukemia cells with the MTS cell viability assay, while, at the same time, showing a dose-dependent decrease in cell number, in contrast to the expected increase in cell number. Possible reasons for this endpoint decoupling/divergence was suggested by Kontar et al (2020). A similar type of focus for the divergent findings with the NRC assay with chloroquine remains to be made.…”
Section: Non-tumor Cellsmentioning
confidence: 67%
See 1 more Smart Citation
“…The antitumor effects of isothiocyanates result from multilevel modification of various biological regulatory pathways. Their efficacy may vary in different neoplastic cells and may induce arrest of cell cycling [11], induction of apoptosis [11], or autophagy [12], as well as many other processes that limit disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…The logP, or the water and n -octanol partition coefficient, is 0.23 ± 0.39 for sulforaphane and 1.77 ± 0.30 for allyl isothiocyanate [ 20 ], indicating that sulforaphane is more hydrophilic than allyl isothiocyanate. This is likely due to differences in the physicochemical properties of the side chains, excluding the ITC group [ 7 , 8 ], and indicates that the nonspecific passage of sulforaphane into the cell is less favorable than that of allyl isothiocyanate; instead, sulforaphane may bind specifically to certain proteins expressed on the cell surface.…”
Section: Discussionmentioning
confidence: 99%